Wayne Rooney my story so far - Rooney, Wayne (HarperSport, 2006)
At just 20 years of age, Wayne Rooney is already one of the best footballers in the world. From his early years in Croxteth, his Premiership debut as a 16-year-old, his ebullient entrance on the international scene in Euro 2004, to the drama of the 2006 World Cup, this is his amazing story so far.